Wielding Gimkit as Formative Assessment Tool in EFL Classroom - Rizal Wahid Permana Putra; Imam Wahyudi Karimullah; Mutmainnah Mustofa (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
Gamification nowadays has increasingly become chart-topping in education. In addition, game-like learning media can possibly be a precise option to use as a formative assessment tool. This research aims at exploring how teacher utilises Gimkit as a formative assessment tool and how students’ perception on the use of Gimkit as a formative assessment tool in English teaching-learning. This research, further, employs a qualitative case approach. The research subject is the ninth grade involving 28 students. The researcher approaches a semi-structured interview to obtain students’ perception on the use of Gimkit as a formative assement in English teaching-learning. The findings reveal that three steps conducted by the teacher in utilising Gimkit; signing up, creating quizes, and implementing Gimkit as a formative assessment in English teaching-learning. Further, it shows that most students have positive perception on the utilisation of Gimkit as a formative assessment in English teaching-learning. These positive values are coded into; Gimkit is considered as an interesting testing tool, it promotes students’ learning motivation and improves students’ reading skill.